Analysis of Information System Governance Audits Based on Cobit 5.0 In Badan Keuangan Daerah City of Salatiga - Ruslie, Gabriella Angeline Yoga; Sulistya Hapsari, Aprina Nugrahesthy (International Journal of Information Technology and Business, 2019)
Badan Keuangan Daerah (BKD) City of Salatiga is a financial governance departement that manages finance including taxes, expenditure and budgeting for Salatiga government. BKD have Sistem Informasi Penatausahaan Keuangan Daerah (SIPKD) that manage all other accounting information systems as input, this system has neverbeen audited before, because KOMINFO has the right to be founded in 2017. The method use is, qualitative describetive with primary data type, and use study case approarch at BKD. Based on audit which researchers do with framework CobIT 5.0, the results of fifth domain at capability level 2 (Managed). In this condition, organization governance to SIPKD already can be support overall, especially in supporting making financial report Salatiga government. Suggestion for next research, can be done at other SKPD in Salatiga